State of the use of gamification elements in software development teams (2017)
One of the fundamental skill that every professional should have, especially in the area of software engineering, is collaborative work, because teams’ members are required to collaborate to develop software. In this environment, one of the techniques currently being used for achieving activities involving collaborative teamwork is gamification. However, there is a lack of techniques to create software development teams through gamification. This paper presents a study of the use of gamification elements in the software engineering environment for collaborative work, in order to identify those elements that can be applied to create highly effective teams for software development. © 2017, Springer International Publishing AG.